Computational Fluid Dynamics Simulation of Airflow Patterns and Particle Deposition Characteristics in Children Upper Respiratory Tracts - Liu, Zhijian; Li, Angui; Xu, Xiaoxia; Gao, Ran (Engineering applications of computational fluid mechanics, 2012)
As findings from studies of airflow patterns and particle deposition in the upper respiratory tracts (URTs) of adults may not be readily extrapolated to studies of the URTs of children, due to the differences in airway anatomy and breathing conditions, the effects of pediatric, physiological features on airflow patterns and particle deposition have been investigated utilizing an idealized model of the URTs of children. Particle deposition characteristics in a 0.01-10 mm spectrum were assessed employing a well-verified, Lagrangian tracking method for different inhalation flow rates, consistent with sedentary (3.5 L/min), light (7.0 L/min) and high (10.5 L/min) activity levels. The main results are: (1) airflow patterns during inhalation and exhalation modes are very different, while airflow patterns are similar during each inhalation or exhalation mode, while subject to three different airflow rates; (2) higher Stokes and impaction numbers are observed in the model for a 3 year old child, when compared to adults under comparably scaled activity levels; and (3) breathing airflow rates, particle diameters and particle densities are three key factors influencing particle deposition rates, with higher deposition rates for children observed when compared to adults under comparable activity levels. For identical impaction parameters, all deposition rates for children are also higher. The localized particle deposition rates in the mouth cavity are similar for children and adults, while those in the larynx, pharynx, trachea and bronchi are higher for children than for adults. Results of this study demonstrate that differences do exist between children and adults in both airflow distribution and aerosol deposition characteristics. These differences should be taken into account in the determination of children's risk exposure levels for airborne toxicants.